Manajemen Humas dalam Membangun Citra Sekolah: Studi Multikasus di SD Muhammadiyyah Pringsewu dan SD IT Cahaya Madani Pringsewu - Astuti, Yani Tri; Diana, Nirva; Hadiati, Eti; Maulidin, Syarif (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2024)
This study aims to examine the urgency of public relations (PR) management in building a positive image for schools, especially in the context of increasingly competitive education. The focus of this research is on two schools in Pringsewu Regency, namely SD Muhammadiyah Pringsewu and SD IT Cahaya Madani Pringsewu, which have distinct characteristics and approaches to PR management. In the digital era and the era of information transparency, the role of PR is crucial in strengthening relationships between schools, communities, and parents, as well as in building a positive image that can enhance the school's reputation in the public eye. The study involved 10 informants, consisting of school principals, vice principals in charge of public relations, teachers, and parents, selected through purposive sampling techniques. Data collection was carried out through in-depth interviews, observation, and documentation. The collected data were analyzed using a qualitative descriptive approach, including the stages of data collection, reduction, categorization, and narrative presentation. To ensure data validity, this study employed source and technique triangulation, rechecking, and verification by experts. The findings indicate that although the two schools differ in their planning and organization of PR activities, both successfully built a positive image through structured PR activities involving collaboration between internal and external stakeholders. SD Muhammadiyah Pringsewu emphasizes publication and close collaboration with the community, while SD IT Cahaya Madani Pringsewu focuses more on school promotion and character development of students. These two approaches demonstrate that effective PR management must be aligned with the vision, mission, and characteristics of each school. The implications of this study highlight that effective PR management can strengthen the relationship between schools and the community, enhance the school's reputation, and positively impact the quality of education delivered. Furthermore, this research contributes to the development of better PR strategies in the context of educational institutions.